RANCANG BANGUN SISTEM INFORMASI BERBASIS WEB PADA DINAS PERTANIAN KOTA PADANG - Defni Defni; Rahmat Rahmat; Rahmat Redha Ilahi (ITP Press)
Rapid development of information technology, the application of information technology is needed both in schools, government and others. Web portal is created at the Department of agriculture to help department of agriculture of Padang field in terms of disseminating information on agricultural service town of Padang . This web is built using PHP and MySQL database. This web can help agencies desert town in storing data associated with agriculture such as agricultural census, agricultural tutorial videos that can be used as a guide by the farmers in the city of Padang . Key words : Information Technology, PHP and MySQL